The Effect of Competency and Work Culture on Security Guard Performance at The Novotel Lombok Hotel - Bobby Yoskar Ndolu; Kemal Taufik; Sri Wahyuningsih (Dinasti Publisher, 2026)
This study aims to analyze the effect of competence and work culture on the performance of the Security Unit at Novotel Lombok Hotel. The Security Unit plays a strategic role in maintaining safety, order, and providing a sense of security and comfort for hotel guests, employees, and assets. Therefore, the performance of the Security Unit must be supported by adequate competence and a positive, sustainable work culture. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to all members of the Security Unit at Novotel Lombok Hotel as the research respondents. The research instruments were tested for validity and reliability prior to further analysis. Multiple linear regression analysis was applied to examine the effects of competence and work culture on the performance of the Security Unit, both partially and simultaneously. The results indicate that competence has a positive and significant effect on the performance of the Security Unit, suggesting that higher levels of competence lead to better performance. In addition, work culture also has a positive and significant effect on performance. Simultaneously, competence and work culture have a significant influence on the performance of the Security Unit at Novotel Lombok Hotel. This study is expected to provide practical contributions for hotel management in formulating human resource management policies, particularly through competence development and the strengthening of work culture to enhance the overall performance of the Security Unit.